Insect galls of Parque Nacional da Serra dos Órgãos (Rio de Janeiro State, Southeastern Brazil) - Valéria Cid Maia; Bernardo Mascarenhas (Papéis Avulsos de Zoologia, 2023)
Abstract The Parque Nacional da Serra dos Órgãos (PARNASO) is an integral protection conservation unit inserted in the domain of the Atlantic forest. This Park was investigated monthly from September to December/2021 and from March to May/2022 for insect galls. Host plants were identified and their exsiccates were deposited in the herbarium (R) of the Museu Nacional. Insects obtained by gall dissection and rearing were deposited in the Entomological Collection of Museu Nacional (MNRJ). The conservational status of the host plants and their origin were verified in the site Flora e Funga do Brasil (2023). New records of host plants in Brazil are presented based on comparison with literature data. PARNASO hosts a great richness of galls (290 gall morphotypes on 43 plant families). Myrtaceae, Melastomataceae, Asteraceae, Fabaceae, and Rubiaceae, Mikania Willd. (Asteraceae), Miconia Ruiz & Pav. (Melastomataceae), and Eugenia L. (Myrtaceae), and Guapira opposita (Nyctaginaceae) were the botanical taxa with the highest number of gall morphotypes, all of them were previously indicated as super hosts in inventories in forest formations of the Atlantic forest, except Rubiaceae. PARNASO includes 148 gall-inducing species native to Brazil, being 69 endemic; among the last 23 are exclusive to the Atlantic forest. Eight gall-inducing species are endangered and four are near threathned. Most galls were found on leaves. The most frequent gall characters were: globoid shape, green color, and glabrous surface. Most galls were induced by Cecidomyiidae (Diptera), however galls of Lepidoptera, Coleoptera, Hemiptera, Thysanoptera, and Hymenoptera wera also found. These are the known patterns in Brazil. The secondary fauna was reported in 62 gall morphotypes and included parasitoids (Hymenoptera), successors (Collembola, Hemiptera and Thysanoptera), cecidophagous (Lepidoptera), and predators (spiders). Parasitoids were the most frequent. Seven gall midge species are recorded for the first time in this Park.